Pre-modern towns at the times of catastrophes
1 online resource (xv, 200 pages)
Keywords: "Covering areas in today's Ukraine, Poland, Bohemia, Moravia, Silesia and Slovakia, this book studies the impact of both natural and human-inflicted disasters on pre-modern towns. This volume is an engaging resource for students and researchers of pre-modern history, social history and disaster studies"--